2019
DOI: 10.3389/fnins.2019.00260
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating Advantages of Neuromorphic Computation: A Pilot Study

Abstract: Neuromorphic devices represent an attempt to mimic aspects of the brain's architecture and dynamics with the aim of replicating its hallmark functional capabilities in terms of computational power, robust learning and energy efficiency. We employ a single-chip prototype of the BrainScaleS 2 neuromorphic system to implement a proof-of-concept demonstration of reward-modulated spike-timing-dependent plasticity in a spiking network that learns to play a simplified version of the Pong video game by smooth pursuit.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 46 publications
0
78
0
1
Order By: Relevance
“…We found that a software simulation (NEST v2.14.0) on an Intel processor (i7-4771), when considering only the numerical state propagation, is at least an order of magnitude slower than our neuromorphic emulation (see Fig. 3 and [5]). Besides this, the emulation on our prototype is at least 1000 times more energy-efficient than the software simulation (23 µJ vs. 106 mJ per iteration).…”
Section: Methodsmentioning
confidence: 74%
“…We found that a software simulation (NEST v2.14.0) on an Intel processor (i7-4771), when considering only the numerical state propagation, is at least an order of magnitude slower than our neuromorphic emulation (see Fig. 3 and [5]). Besides this, the emulation on our prototype is at least 1000 times more energy-efficient than the software simulation (23 µJ vs. 106 mJ per iteration).…”
Section: Methodsmentioning
confidence: 74%
“…Neuromorphic computing was coined by Mead, when he envisioned that while exploiting the similarities between semiconductor physics and biological neural systems, one may develop brain‐inspired computing platforms. Ever since, neuromorphic research has evolved and researchers are implementing various technologies, from conventional semiconductors, as proposed by Mead, to memristive systems, to hybrid CMOS–memristive designs to develop neuro‐mimicking platforms for replicating experimental results observed in biology or for neuro‐inspired platforms used in computing systems …”
Section: Introductionmentioning
confidence: 99%
“…Ultimately we come to the conclusion that while general-purpose computing has, until now, largely been able to deliver high performance, the next generation of brain tissue simulation will be severely limited by hardware bottlenecks. Indeed this trend was already foreshadowed in empirical studies (Jordan et al 2018), and solutions involving hardware accelerators such as General Purpose Graphical Processing Units (GPGPUs) have been proposed (Fidjeland et al 2009;Yavuz et al 2016;Brette and Goodman 2012), while the development of custom brain-like hardware is being actively explored with promising results (van Albada et al 2018;Wunderlich et al 2018).…”
Section: Introductionmentioning
confidence: 99%